2022
DOI: 10.12669/pjms.38.4.5830
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of proximal femoral nail antirotation and total hip arthroplasty in the treatment of femoral intertrochanteric fracture

Abstract: Objectives: To investigate the effects of proximal femoral nail antirotation (PFNA) and total hip arthroplasty for the treatment of femoral intertrochanteric fractures. Methods: Clinical data from 110 femoral intertrochanteric fracture patients treated at our hospital between January 2019 and July 2020 were analyzed retrospectively. Patients were divided into two groups based on the type of surgical intervention used. One group included patients (n= 59) who had undergone PFNA internal fixation and anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Hip fractures (HFs) are common orthopedic events in clinical settings, especially in elderly population. 1 About 95 % of all HFs are due to falls 2 with the estimated annual global prevalence of 4.5 million by 2050. 3 HFs are particularly dangerous in the geriatric patients, with high (nearly 30%) mortality within a year after the fracture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hip fractures (HFs) are common orthopedic events in clinical settings, especially in elderly population. 1 About 95 % of all HFs are due to falls 2 with the estimated annual global prevalence of 4.5 million by 2050. 3 HFs are particularly dangerous in the geriatric patients, with high (nearly 30%) mortality within a year after the fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the developed countries with a high income, most HFs are treated surgically, with hospitalization and subsequent rehabilitation. 1 Spinal anesthesia is routinely used for HF surgery since it is associated with reduced operative time, less bleeding, and lower rate of complications. 8 , 9 However, the choice of anesthesia for elderly hip fracture surgery remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Therefore, the goal of the treatment should be to reduce the mortality and restore the function of the hip joint as soon as possible to promote independent mobility. 5 …”
Section: Introductionmentioning
confidence: 99%
“… 6 Its biomechanical advantages and avoidance of periosteum peeling can effectively promote fracture healing. 5 , 6 InterTAN and PFNA are commonly used intramedullary fixation techniques. 7 InterTAN head and neck screws feature a high anti-rotation ability due to their interlocking combination design.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The location of acetabular fracture is generally deep in anatomy, with the distribution of a large number of nerves and blood vessels around, resulting in difficult surgical exposure and reduction. 2 The majority of patients with acetabular fracture have poor clinical prognosis. 3 It has been reported that appropriate surgical approach can significantly improve the surgical effect of acetabular fracture and improve the prognosis of patients with fracture.…”
Section: Introductionmentioning
confidence: 99%